Cardiomyocyte Atrophy, an Underestimated Contributor in Doxorubicin-Induced Cardiotoxicity - Chen, De-Shu; Yan, Jing; Yang, Ping-Zhen (Frontiers in Cardiovascular Medicine, 2022)
Left ventricular (LV) mass loss is prevalent in doxorubicin (DOX)-induced cardiotoxicity and is responsible for the progressive decline of cardiac function. Comparing with the well-studied role of cell death, the part of cardiomyocyte atrophy (CMA) playing in the LV mass loss is underestimated and the knowledge of the underlying mechanism is still limited. In this review, we summarized the recent advances in the DOX-induced CMA. We found that the CMA caused by DOX is associated with the upregulation of FOXOs and “atrogenes,” the activation of transient receptor potential canonical 3-NADPH oxidase 2 (TRPC3-Nox2) axis, and the suppression of IGF-1-PI3K signaling pathway. The imbalance of anabolic and catabolic process may be the common final pathway of these mechanisms. At last, we provided some strategies that have been demonstrated to alleviate the DOX-induced CMA in animal models.